The Extent to Which Land Conflicts Affect Food Security: A Case of Kasese District, Western Uganda - Tinkasimire, Cleous Bwambale; Mwine, Julius; Musinguzi, Peter S. (Education, 2023)
This study investigated the effect of land conflicts on food security in Kasese district, Western Uganda in 2018. Exploratory and descriptive research survey designs were adopted using a population of 1999 and sample size of 445. Self administered questionnaires, interview guides and documentary checklists were used to collect data from the field. Majority respondents 92.5% revealed that there's inequitable distribution of land among individuals and ethnic groups; 62.2 % of land is owned by men; 71.1% of the population depended on small scale farming; 91.75% agreed that there was restriction on utilization of government owned land; and 89.5% agreed that land conflicts destabilize food production. The proportion of causes of land conflicts differed which ranked in the order; protection of minority groups 35.9%, survival tendencies 24.4%, quick cash 21%, and investment 18%. The study concluded that: the major cause of land conflict is inadequate distribution and that there was no strong relationship between land conflicts and food sustainability. The gaps in Ugandan land laws and policies are the breed birth of land conflicts in Kasese district. The study recommended comprehensive review of the existing land laws, policies and apportioning part of government owned land to increase land access in Kasese district. The community-based arbitration units like local councils should be empowered to handle land related disputes to ease access to quick justice. Finally, the stakeholders should intensify community awareness levels on sustainable food production, nutrition and optimum land use through a multi-sectoral food security approach to ensure peaceful co-existence in Kasese.
Keywords: Conflict; Land; Food; Food Security; Food Sustainability